The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1021/acsami.2c17490
|View full text |Cite
|
Sign up to set email alerts
|

Small-Molecule Electron Transport Layer with Siloxane-Functionalized Side Chains for Nonfullerene Organic Solar Cells

Abstract: Active layer materials with silicone side chains have been broadly reported to have excellent long-term stability in harsh environments. However, the application of conjugated materials with silicone side chains in electron transport layers (ETLs) has rarely been reported. In this research, we synthesized for the first time a siloxane-modified perylene-diimide derivative (PDI-OSi) consisting of a side-chain substituent of siloxane and a conjugated group of perylene-diimide (PDI). The inserted siloxane function… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 64 publications
0
8
0
Order By: Relevance
“…This interaction enhances the electron affinity of the molecule, thus promoting the efficient transfer of electrons. When acting as CILs, they can form an intermolecular electric field (IEF) from the active layer to the CIL at the active layer/cathode interface, which can effectively facilitate the transport of electrons from the active layer to the cathode. , According to the results of theoretical calculation (Figure S12), it can be observed that the lowest unoccupied molecular orbitals (LUMO) of PFPy-BT and PFPy-TTBT molecules are principally concentrated in the benzothiadiazole unit, while the highest occupied molecular orbitals (HOMO) are primarily concentrated in the conjugate main chain. In contrast, the HOMO and LUMO of PFPy-TT are concentrated in the polymer backbone.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This interaction enhances the electron affinity of the molecule, thus promoting the efficient transfer of electrons. When acting as CILs, they can form an intermolecular electric field (IEF) from the active layer to the CIL at the active layer/cathode interface, which can effectively facilitate the transport of electrons from the active layer to the cathode. , According to the results of theoretical calculation (Figure S12), it can be observed that the lowest unoccupied molecular orbitals (LUMO) of PFPy-BT and PFPy-TTBT molecules are principally concentrated in the benzothiadiazole unit, while the highest occupied molecular orbitals (HOMO) are primarily concentrated in the conjugate main chain. In contrast, the HOMO and LUMO of PFPy-TT are concentrated in the polymer backbone.…”
Section: Resultsmentioning
confidence: 99%
“…When acting as CILs, they can form an intermolecular electric field (IEF) from the active layer to the CIL at the active layer/cathode interface, which can effectively facilitate the transport of electrons from the active layer to the cathode. 26,66 According to the results of theoretical 34 In contrast to the UV−vis spectra of PFPy-BT and PFPy-TTBT in solutions, redshifts are found in the corresponding film spectra due to molecular aggregation.…”
Section: Density Functional Theory Calculations For Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, PDI's imide and bay sites benet greatly from the addition of branched alkyl chains or aromatic groups. [94][95][96][97][98] Moreover, the incorporation of heteroatoms into the perylene-conjugated skeleton produces donor/acceptor surfaces with increased electrical interactions, which in turn reduces the amount of energy required to bind polaron pairs. An efficient method for controlling optical absorption and other properties, such as energy level, charge transport, and crystallinity, is to use a conjugated linker or bridge as a link between multiple PDI moieties in twisted 2D/3D.…”
Section: Shi-yong Liumentioning
confidence: 99%
“…Side‐chain engineering can help adjust the crystallinity of PDMs to further improve their stability. [ 106 ] Developing active layer materials, [ 107 ] interfacial engineering, [ 108 ] and optimizing processing technology [ 109 ] are practical paths to accelerate device stability by optimizing interfacial morphology. In addition, proper packaging of the OSCs is a pivotal technology to avoid instability caused by high humidity and oxygen.…”
Section: Polymer Donor Materials Based On Bdtmentioning
confidence: 99%